Corporate Governance Reporting in Accordance with SIN at the Warsaw Stock Exchange - Błażyńska, Joanna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The paper presents the results of a study on whether the non-financial statements (reports) report information on corporate governance in accordance with the assumptions of the SIN standard; and if so, to what extent. Declarations of the companies listed on the Warsaw Stock Exchange are drafted in accordance with the SIN standard. Research Design & Methods: The research covered all companies that prepared reports in the years 2017–2019 – 21 listed companies and 59 reports (it was assumed the companies prepared a report in 2019). Content analysis, descriptive and comparative analysis, and induction were used. Findings: The research shows that SIN standards do not actually translate into practice. Not all the listed companies have a separate management area (14%). Only 43% of companies include Key Performance Indicators and only one company used the materiality matrix. Implications / Recommendations: The study shows that there is cause for concern. Only three non-financial statements (reports) meet the SIN standards to the extent that they can be considered useful for stakeholders. The companies do not understand the idea of linking corporate governance with non-financial (social, environmental) aspects of their business. Contribution: The research contributes to the research gap surrounding the disclosure of non-financial information in annual reports.